2018
DOI: 10.1093/ajcn/nqy147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a (poly)phenol-rich extract from the brown algae Ascophyllum nodosum on DNA damage and antioxidant activity in an overweight or obese population: a randomized controlled trial

Abstract: Background Epidemiologic evidence suggests that a diet rich in (poly)phenols has beneficial effects on many chronic diseases. Brown seaweed is a rich source of (poly)phenols. Objective The aim of this study was to investigate the bioavailability and effect of a brown seaweed (Ascophyllum nodosum) (poly)phenol extract on DNA damage, oxidative stress, and inflammation in vivo. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 54 publications
0
49
0
Order By: Relevance
“…In this study, we investigated the effects of the five-week administration of the phytocomplex obtained from two brown algae, A. nodosum and F. vesiculosus, on glycemic control and liver function of HFD-treated Wistar rats. Several studies have confirmed the multiple beneficial effects of seaweed products, since their bioactive components have antidiabetic, antiobesity, and antioxidant properties [4,13,[16][17][18][19][20]. A recent study reported that ascophyllan from A. nodosum is able to induce glucagon-like peptide-1 (GLP-1) secretion from human intestinal cells, suggesting that it may represent a useful agent for controlling blood glucose in humans [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the effects of the five-week administration of the phytocomplex obtained from two brown algae, A. nodosum and F. vesiculosus, on glycemic control and liver function of HFD-treated Wistar rats. Several studies have confirmed the multiple beneficial effects of seaweed products, since their bioactive components have antidiabetic, antiobesity, and antioxidant properties [4,13,[16][17][18][19][20]. A recent study reported that ascophyllan from A. nodosum is able to induce glucagon-like peptide-1 (GLP-1) secretion from human intestinal cells, suggesting that it may represent a useful agent for controlling blood glucose in humans [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxytrifuhalol A, 7-hydroxyeckol, C-O-C dimer of phloroglucinol, diphloroethol, fucophloroethol, dioxinodehydroeckol, and/or their glucuronides or sulfate esters (Additional file 1: Figure S1) were selected as candidate BFIs for brown seaweed because of their apparent specificity and their suitable postprandial kinetics [20,21]. Fucoxanthinol, a metabolite of fucoxanthin, has also been found in plasma from a study after only a single oral dose of brown seaweed, making it interesting also as a candidate short-term biomarker [22].…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Corona et al, there were substantial differences among volunteers in their pattern and extent of phlorotannin metabolism [20]. The total level of phlorotannins and their metabolites ranged from 0.01 to 7.8 μg/ ml and from 0.15 to 33.5 μg/ml quantified as phloroglucinol equivalents in urine and plasma, respectively [20], while the range extended from 0.13 to 522.09 μg/ml quantified as phloroglucinol equivalents in urine in another study [21]. The large inter-individual differences have been attributed to variation in the microbiota composition in the colon and to differences in expression of phase II metabolizing enzymes [46,54], suggesting large inter-individual variation in metabolite kinetics and, consequently, in their potential usefulness as BFIs for quantitative intake assessment.…”
Section: Brown Seaweed Biomarkers Phlorotanninsmentioning
confidence: 89%
See 1 more Smart Citation
“…Higher oxidant status increases the oxidative damage of macromolecules, which, associated with obesity, increases the probability of chronic disease development [167], with obese individuals as a risk group. Baldrick et al [168] investigated the bioavailability and effect of an Ascophyllum nodosum (Linnaeus) Le Jolis polyphenol-rich extract on DNA damage, oxidative stress, and inflammation level. Eighty participants, of which 36 were obese, consumed daily, for eight weeks, a capsule containing 100 mg of Ascophyllum nodosum (Linnaeus) Le Jolis polyphenol-rich extract.…”
Section: Clinical Trialsmentioning
confidence: 99%